Antimalarial and mosquito repellent plants: insights from Burundi - Havyarimana, Célestin; Nkengurutse , Jacques; Ngezahayo , Jérémie; Aida , Cuni-Sanchez; Masharabu, Tatien (Ethnobotany Research and Applications, 2023)
Background: The present ethnobotanical study was conducted to identify plant species used by Burundians to treat malaria and to repel mosquitoes, to compare this with available literature, to identify species which could be further investigated and to discuss potential future promotion or cultivation. Methods: Surveys were conducted between April and October 2018 in 7 provinces representing the 5 ecological zones of Burundi. A semi-structured questionnaire was administered to 341 respondents randomly selected (between 25 and 50 household heads in each province). Results: A total of 44 plant species were reported in this study: 32 as antimalarial, 2 as mosquito repellents and 10 for both purposes. Leaves were the most used plant part for antimalarial plants (84%) and for mosquito repellent plants (88%). According to the respondents, 28 plant species were being cultivated and 16 were mostly collected from the wild. An overview of literature on some plant species cited in this study showed that 8 plant species were not reported in previous studies. Conclusions: This study highlighted the use of antimalarial and mosquito repellent plants in Burundi. Its interest is to be a database of antimalarial and mosquito repellent plants. It will help in decision-making regarding traditional medicine development and medicinal plants conservation. Keywords: Ethnobotany; antimalarial activity; mosquito repellents; plants cultivation; Eco-climatic zones.